Beyond LKB1 Mutations in Non-Small Cell Lung Cancer: Defining LKB1less Phenotype to Optimize Patient Selection and Treatment - Cristina Borzi; Giulia Galli; Monica Ganzinelli; Diego Signorelli; Claudio Vernieri; Marina Chiara Garassino; Gabriella Sozzi; Massimo Moro (Pharmaceuticals, 2020)
LKB1 is frequently mutated in non-small cell lung cancer (NSCLC). LKB1-mutated NSCLCs often have a dismal prognosis and receive lower benefit from the currently available therapies. LKB1 acts as a cell emergency brake in low-energy conditions, by modulating the activity of crucial anabolic enzymes. Thus, loss of LKB1 activity leads to the enhancement of tumor cell proliferation also under conditions of energy shortage. This unrestrained growth may be exploited as an Achilles heel in NSCLC, i.e., by inhibiting mitochondrial respiration. Recently, clinical trials have started to investigate the efficacy of metabolism-based treatments in NSCLCs. To date, enrollment of patients within these trials is based on LKB1 loss of function status, defined by mutation in the gene or by complete absence of immunohistochemical staining. However, LKB1 impairment could be the consequence of epigenetic regulations that partially or completely abrogate protein expression. These epigenetic regulations result in LKB1 wild-type tumors with aggressiveness and vulnerabilities similar to those of LKB1-mutated ones. In this review, we introduced the definition of the “LKB1less phenotype”, and we summarized all currently known features linked to this status, in order to optimize selection and treatment of NSCLC patients with impaired LKB1 function.